HOW RISK MANAGEMENT CAN BE IMPLEMENTED IN NEW AGRO-PRODUCT DEVELOPMENT (NAPD)?: A SYSTEMATIC LITERATURE REVIEW - Lu'ayya, Naila Maulidina; Santoso, Imam; Mustaniroh, Siti Asmaul; Wafi'uddin, Izzum; Choirun, Annisa'u (Jurnal Teknologi Pertanian, 2024)
New product development is highly complex because it integrates technical challenges from both internal and external sources. The potential for uncertainty or failure exists at every step of the product development process. One of the important tools to minimize risks in product development is risk management in new product development. This paper aims to review some research literature on the concept, process, and category of risk management in new agro-product development. This research uses a literature review analysis to analyze the concept and process of risk management in new product development. The articles were selected from Emerald, Elsevier, Springer, MDPI, and Taylor & Francis databases. The findings of this study demonstrate the critical role of risk management in minimizing risks associated with new product development through the implementation of diverse strategies. Risk management involves identifying, analyzing, evaluating, and treating risks. A variety of internal and external factors influence risk in product development. Internal factors are design, production, financial, management (organizational), marketing, market, technology, and supplier risks. External factors include suppliers, customers, and retailers outside the company. Many businesses, including small and medium-sized enterprises (SMEs), have adopted risk management to prevent product failures and financial losses. This paper provides a research framework for applying risk management to new agroindustrial product development.